1995
DOI: 10.1016/0014-5793(95)01001-u
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of protein kinase in Δ12‐prostaglandin J2‐induced expression of rat heme oxygenase‐1 gene

Abstract: Furthermore, the nuclear protein binding to the element was suppressed by in vitro phosphatase treatment of the nuclear proteins from A~2-PGJ2-treated cells. These findings suggest that A12-PGJ 2 induces the expression of the HO-I gene through phosphorylation of the nuclear proteins which bind to the A~z-PGJ zresponsive element.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…We demonstrated that the induction of HO-1 expression in HMEC-1 treated with 15d-PGJ 2 was mediated by the activation of HO-1 promoter, but not by the stabilization of HO-1 mRNA. The increased transcriptional activity of HO-1 promoter in response to another prostaglandin-J 2 derivative, 12d-PGJ 2 , was earlier observed in aortic endothelial cells and basophilic leukemia cells (25,34). Koizumi and colleagues showed that 12d-PGJ 2 induces the expression of the rat HO-1 gene through the phosphorylation of the nuclear proteins, which bind to the specific 12d-PGJ 2 responsive element located in HO-1 promoter (25,34).…”
Section: Discussionmentioning
confidence: 87%
“…We demonstrated that the induction of HO-1 expression in HMEC-1 treated with 15d-PGJ 2 was mediated by the activation of HO-1 promoter, but not by the stabilization of HO-1 mRNA. The increased transcriptional activity of HO-1 promoter in response to another prostaglandin-J 2 derivative, 12d-PGJ 2 , was earlier observed in aortic endothelial cells and basophilic leukemia cells (25,34). Koizumi and colleagues showed that 12d-PGJ 2 induces the expression of the rat HO-1 gene through the phosphorylation of the nuclear proteins, which bind to the specific 12d-PGJ 2 responsive element located in HO-1 promoter (25,34).…”
Section: Discussionmentioning
confidence: 87%
“…A previous study failed to find changes in CO during histamine-induced bronchoconstriction, but this association only was explored in five patients (32). The increase of COex during histamine-induced bronchoconstriction could be due to the activation of OH-1 by prostaglandins released by mast cells (33) or by the changes in airway caliber. The increase of COex in subjects without response to histamine challenge could be justified by a subclinical bronchoconstriction, without change in FEV 1 , or by oxidative stress promoted by saline solution.…”
Section: Discussionmentioning
confidence: 94%
“…The activation of HO-1 by prostaglandins [30] released by mast cells during the early asthmatic reaction [3,31] may explain the elevated levels of exhaled CO during this phase. The absence of significant changes in exhaled NO levels is possibly due to the inability of prostaglandins and other compounds released during the early reaction, such as leukotrienes and histamine, to activate iNOS.…”
Section: Discussionmentioning
confidence: 99%